Analisis dan Perancangan Aplikasi Berbasis Web untuk Pengelolaan Harga Pokok Produksi Menggunakan Metode Harga Pokok Proses - Magdalena Karismariyanti (STMIK Sinar Nusantara, 2019)
Manufacturing of products incurred raw material costs, direct labor costs, and factory overhead costs, which could be used to determine the price of the product sold. On the contrary, the company, which manufactured thousands of toys and dolls monthly, did not have proper cost record. Production cost calculated by the average of total cost divided with a total of confirmed product. Hence, the production cost for each product could not be defined precisely. Based on the problems described, a web application was developed to manage the recording of transaction and automatically calculated the cost of production. This application's functionalities were able to manage purchasing activities, handing over raw materials to production, confirming finished goods, calculating production costs, posting journals and ledgers, and reporting of the cost of production. This application could help companies to calculate the unit cost. Based on a comparison between manual and application testing, it could be concluded that output in the application displayed an exact match from the manual. Thus, this web-based application was ready to be implemented in the company.